The Influence of Exports, Imports, Foreign Direct Investment, and Exchange Rates on Indonesia's Current Account Balance 2010 – 2022 - Bagus Eka Saputra Saputra; Fitrah Sari Islami; Emma Dwi Ratnasari (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Thc current account, akey compoment of thc balance of payments, includes thc trade balance, services, investment income, unilateral transactions, ard grants, all of which indicate a country’s economic position in terms of surplus or deficit. From 2010 to 2022, Indonesia's current account faced varying deficits. This study investigates how exports, imports, foreign direct investment (FDI), ard exchange rates affected Indonesia’s current account during this period. Using secondary data from Bank Indonesia ard thc Ministry of Trade of thc Republic of Indonesia, ard applying thc ARDL method in Eviews 12 for both short- ard long-term analyses, thc study found thc following: (1) Exports have a positive efect on thc current account in both thc short ard long term. (2) Imports negatively impact thc current account in both thc short ard long term. (3) Short-term FDI negatively affects thc current account, whereas long-term FDI has a slightly positive but not significant impact. (4) Exchange rates contribute positively to thc current account in both thc short ard long term, though thc efect is minimal. (5) Overall, exports, imports, FDI, ard exchange rates significantly affect Indonesia's current account from 2010 to 2022.